Excitation energy-dependent nature of Raman scattering spectrum in GaInNAs/GaAs quantum well structures - Erol, Ayşe; Akalın, Elif; Sarcan, Fahrettin; Dönmez, Ömer; Arıkan, Mehmet Çetin; Puustinen, Janne; Guina, Mircea; AKYÜZ, SEVİM (Springer, 233 Spring St, New York, Ny 10013 Usa, 2012)
The excitation energy-dependent nature of Raman scattering spectrum, vibration, electronic or both, has been studied using different excitation sources on as-grown and annealed n- and p-type modulation-doped Ga1 -aEuro parts per thousand x In (x) N (y) As1 -aEuro parts per thousand y /GaAs quantum well structures. The samples were grown by molecular beam technique with different N concentrations (y = 0%, 0.9%, 1.2%, 1.7%) at the same In concentration of 32%. Micro-Raman measurements have been carried out using 532 and 758 nm lines of diode lasers, and the 1064 nm line of the Nd-YAG laser has been used for Fourier transform-Raman scattering measurements. Raman scattering measurements with different excitation sources have revealed that the excitation energy is the decisive mechanism on the nature of the Raman scattering spectrum. When the excitation energy is close to the electronic band gap energy of any constituent semiconductor materials in the sample, electronic transition dominates the spectrum, leading to a very broad peak. In the condition that the excitation energy is much higher than the band gap energy, only vibrational modes contribute to the Raman scattering spectrum of the samples. Line shapes of the Raman scattering spectrum with the 785 and 1064 nm lines of lasers have been observed to be very broad peaks, whose absolute peak energy values are in good agreement with the ones obtained from photoluminescence measurements. On the other hand, Raman scattering spectrum with the 532 nm line has exhibited only vibrational modes. As a complementary tool of Raman scattering measurements with the excitation source of 532 nm, which shows weak vibrational transitions, attenuated total reflectance infrared spectroscopy has been also carried out. The results exhibited that the nature of the Raman scattering spectrum is strongly excitation energy-dependent, and with suitable excitation energy, electronic and/or vibrational transitions can be investigated.
Keywords: GaInNAs; Photoluminescence; Raman; FT-Raman; FT-IR; Local modes; inplane photovoltage; nitrogen; gainasn; alloys; fotolüminesans; yerel modları; düzlem içi photovoltage; azot; alaşımlar